KURIKULUM TAUHIDI UNIVERSITAS ISLAM (Refleksi Terhadap Insan Kamil di Bidang Pendidikan) - asmu'i marto (Dirosat : Journal of Islamic Studies, 2016)
As the most important medium of developing civilization, Islamic University should be able to reflect on human figure which reflects the nature of God. The human being is the center of civilization. Human figure who could build the civilized human civilization is the figure who reflects the nature of God. This man is known by term insan kamil. Fundamentally, the structure and curriculum of Islamic University should be taken from the nature of man which consists permanent and spiritual dimension as well as material and emotional dimension. Then in practical level, research activities in the educational activities should involve various methods, such as religious and scientific, empirical and rational, deductive and inductive, subjective and objective, without making one method is more dominant than the other. Because of the University’s curriculum-based involve all ‘civilized human beings’ potential in a whole organ intact and holistic, then it is called tauhidi curriculum. In short, the Islamic University is a reflection of the insan kamil or universal human being (al-insān al-kullīor al-insān al-kāmil), which is directed to form a human figure perfectly and completely.